Trends in the coprescription of proton pump inhibitors with clopidogrel: an ecological analysis - Juurlink, David N. (CMAJ Open, 2015)
BACKGROUND: In early 2009, 2 observational studies and a US Food and Drug Administration (FDA) advisory addressed the drug interaction between proton pump inhibitors (PPIs) and clopidogrel. One study suggested that pantoprazole could be used safely in this setting, whereas the other study and the FDA advisory did not distinguish among PPIs. We examined trends in PPI prescribing among clopidogrel recipients in the period following these events. METHODS: We conducted a population-based time series analysis of Ontario residents aged 66 years or older for whom clopidogrel was prescribed between Apr. 1, 1999, and Sept. 30, 2013. We determined the proportion of clopidogrel recipients dispensed a PPI during each quarter and the proportions who received pantoprazole or other PPIs. The outcome of interest was change in the use of pantoprazole. RESULTS: In the final quarter of 2008, pantoprazole represented 23.7% of all PPI prescriptions dispensed to patients receiving clopidogrel. Following the publications and FDA advisory in early 2009, pantoprazole use increased substantially. By the end of 2009, this medication accounted for 52.5% of all PPI prescriptions issued to patients receiving clopidogrel; by the end of the study period, it accounted for 71.0% of all PPI prescriptions dispensed to such patients (p < 0. 001). We also observed a modest drop in overall PPI use among clopidogrel recipients beginning in early 2009. INTERPRETATION: In 2009, the prescribing of PPIs with clopidogrel changed substantially in Ontario, with pantoprazole rapidly becoming the most commonly prescribed agent in its class. However, a modest decline in overall PPI use also occurred that may reflect suboptimal translation of emerging drug safety information to clinical practice.